yes they are congruent with ASA
Find the Greatest Common Factor (GCF)
<u>GCF = 6y^6</u>
Factor out the GCF. (Write the GCF first. Then, in parenthesis divide each term by the GCF.)
6y^6(24y^8/6y^6 + 6y^6/6y^6)
Simplify each term in parenthesis
<u>6y^6(4y^2 + 1)</u>
![\frac{3x-5}{x-5}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3x-5%7D%7Bx-5%7D%20)
> 0
First, note that x is undefined at 5. / x ≠ 5
Second, replace the inequality sign with an equal sign so that we can solve it like a normal equation. / Your problem should look like:
![\frac{3x-5}{x-5}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3x-5%7D%7Bx-5%7D%20)
= 0
Third, multiply both sides by x - 5. / Your problem should look like: 3x - 5 = 0
Forth, add 5 to both sides. / Your problem should look like: 3x = 5
Fifth, divide both sides by 3. / Your problem should look like: x =
Sixth, from the values of x above, we have these 3 intervals to test:
x <
![\frac{5}{3}](https://tex.z-dn.net/?f=%20%5Cfrac%7B5%7D%7B3%7D%20)
![\frac{5}{3}](https://tex.z-dn.net/?f=%20%5Cfrac%7B5%7D%7B3%7D%20)
< x < 5
x > 5
Seventh, pick a test point for each interval.
1. For the interval x <
![\frac{5}{3}](https://tex.z-dn.net/?f=%20%5Cfrac%7B5%7D%7B3%7D%20)
:
Let's pick x - 0. Then,
![\frac{3x0-5}{0-5}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3x0-5%7D%7B0-5%7D%20)
> 0
After simplifying, we get 1 > 0 which is true.
Keep this interval.
2. For the interval
![\frac{5}{3}](https://tex.z-dn.net/?f=%20%5Cfrac%7B5%7D%7B3%7D%20)
< x < 5:
Let's pick x = 2. Then,
![\frac{3x2-5}{2-5}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3x2-5%7D%7B2-5%7D%20)
> 0
After simplifying, we get -0.3333 > 0, which is false.
Drop this interval.
3. For the interval x > 5:
Let's pick x = 6. Then,
![\frac{3x6-5}{6-5}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3x6-5%7D%7B6-5%7D%20)
> 0
After simplifying, we get 13 > 0, which is ture.
Keep this interval.
Eighth, therefore, x <
![\frac{5}{3}](https://tex.z-dn.net/?f=%20%5Cfrac%7B5%7D%7B3%7D%20)
and x > 5
Answer: x <
![\frac{5}{3}](https://tex.z-dn.net/?f=%20%5Cfrac%7B5%7D%7B3%7D%20)
and x > 5
Answer:
![Rx+Py=RP](https://tex.z-dn.net/?f=Rx%2BPy%3DRP)
Step-by-step explanation:
The points on the straight line are (P, 0) and (0, R).
The slope would be
![m=\frac{R-0}{0-P}=-\frac{R}{P}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7BR-0%7D%7B0-P%7D%3D-%5Cfrac%7BR%7D%7BP%7D)
And
, because the y-intercept is at (0, R).
So, the equation of this line would be
![y=-\frac{R}{P} x+R](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7BR%7D%7BP%7D%20x%2BR)
Where we multiply the equation by ![P](https://tex.z-dn.net/?f=P)
![Py=-Rx+RP](https://tex.z-dn.net/?f=Py%3D-Rx%2BRP)
Therefore, the equation that represents this line is
![Rx+Py=RP](https://tex.z-dn.net/?f=Rx%2BPy%3DRP)
<h2>
So, the right answer is B.</h2>
Answer:
the answer is 1
Step-by-step explanation:
the answer is 1